The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1103/physrevb.58.5157
|View full text |Cite
|
Sign up to set email alerts
|

Quartz-crystal microbalance studies of the velocity dependence of interfacial friction

Abstract: We have employed a quartz-crystal microbalance technique to measure the vibrational amplitude dependence of quality factor shifts which occur when Kr monolayers adsorb on the microbalance's gold electrodes. Assuming that the friction force is proportional to some power of the sliding velocity of the film relative to its substrate, such measurements allow one to infer whether or not the friction force law is linear in form. We have observed a linear friction law to be valid for a full monolayer of both liquid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 14 publications
1
21
0
Order By: Relevance
“…They showed t s was constant over a wide range of frequency and amplitude. The frequency is difficult to vary in experiment, but Mak and Krim (1998) found that t s was independent of amplitude in both fluid and crystalline phases of Kr on Au. Tomassone et al (1997) have used two additional techniques to determine t s .…”
Section: E Frenkel-kontorova Model In Two Dimensions: Adsorbed Monolmentioning
confidence: 99%
“…They showed t s was constant over a wide range of frequency and amplitude. The frequency is difficult to vary in experiment, but Mak and Krim (1998) found that t s was independent of amplitude in both fluid and crystalline phases of Kr on Au. Tomassone et al (1997) have used two additional techniques to determine t s .…”
Section: E Frenkel-kontorova Model In Two Dimensions: Adsorbed Monolmentioning
confidence: 99%
“…2d). This model is extensively used for the interpretation of nanotribological experiments with the QCM [20]. We consider the drag coefficient of the dashpot,ξ S , to be a fixed parameter independent of frequency.…”
Section: Loading With a Mass In Series With A Dashpotmentioning
confidence: 99%
“…Nanotribology has also gained much from the QCM, where the early work has been done by J. Krim [19,20]. The Krim group studied adsorbed monolayers of noble gas atoms onto the electrode and observed an increase in dissipation.…”
Section: Introductionmentioning
confidence: 98%
“…The possibility of slip was discussed until recently, in mainstream literature, only in the context of the flow of polymer melts [11,12], though over the years persistent doubts were expressed [13]. No-slip contrasts with slip characteristic of highly viscous polymers [11,12], monolayers of gas condensed on vibrated solids [14], superfluid helium [15], moving contact lines of liquid droplets on solids [16], and kinetic friction of liquid films less than 5-10 molecular dimensions thick [17,18]. However, experimental capability and technical needs have changed -especially so with the emerging interest in microfluidics and microelectromechanical system (MEMS)-based devices.…”
Section: Hydrodynamic Force Of Fluids Flowing In Microto Nanofluidicsmentioning
confidence: 99%